This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 5. Using algebraic equations, prove: ((Forall x. f(x)) -> (Exists y. g(y))) = (Exists x. Exists y. (f(x) -> g( 6. Using algebraic equations, prove: ((Forall x. (f(x) -> h(x))) /\ (Forall x. (g(x) -> h(x)))) = (Forall x. ((f 7. Suppose that, given an sequence xs and any value x whose type is the same as the type of the e What To Turn In * A paper with solutions to the required problems (staple multiple sheets together - no paper clips). * No files or Haskell sessions are required....
View Full Document
- Spring '08